Institutional restrictions on access to credit for coffee growing in Honduras. An analysis based on the economic theory of Douglass North (Journal of Management & Business, 2022)
This research deals with the knowledge of institutional restrictions, which have a bearing on access to credit for the agro-export sector and, in this case, is addressed to producers in the coffee industry in Honduras. The focus is to contribute and understand the relationships between the actors in the financial system, the inconveniences that can occur due to lack of information and how they affect producers. As a consequence, they are unable to access public and private sources as options for financial services with better credit conditions in the capital market. Due to the norms referred to the institutional economy, the different options are analyzed through a bibliographic review, finding legislations, regulations, rules, circulars, financial products, among others, which are indispensable on the way to the financial leverage of their activities. Thus, it is proposed to focus on implementing a value system integrated by all the actors of the coffee industry to achieve access to credit, which leads to generate confidence and guarantee the return of loans in a secure manner.
Keywords: Seleccionado:institutional restrictions, access to credit, value chain